Sequencing and phylogenetic analysis of the SLC11A1 gene in pigs. Issue 1 (1st January 2017) - Devi, Bhanita; Laskar, Subimal; Borah, Prabodh; Hussain, Iftikar; Bharti, Panch Kishor
ABSTRACT: The solute carrier family 11 member A1 ( SLC11A1 ), also known as natural resistance-associated macrophage protein 1 ( NRAMP1 ), is a divalent transition metal (iron and manganese) transporter involved in iron metabolism and host resistance to certain pathogens. To study the genetic diversity of the SLC11A1 gene in Doom pigs of Assam especially on its evolution and differentiation within and among species, the partial sequence of the SLC11A1 gene was sequenced, characterized and compared with other published sequences of pigs and other species livestock. The gene sequence of Doom pigs showed the highest sequence identity with EF200584.1 (exotic pig) and the lowest similarity AY368475.1 (large white strain 008). One single nucleotide polymorphism (SNP) was identified in the heterozygous sequence at the 736 bp position (A→G). The sequence showed the highest sequence identity (81.74%) with that of O. aries and the lowest similarity (39.12%) with B. bubalis (Mehsana breed), respectively. Phylogenetic analysis revealed that the Doom pig is more closely related to EU135795.1 (Chinese local pig) and EF200584.1 (Pig, Iowa State University). The sequencing and phylogenetic analysis of the SLC11A1 gene of Doom pigs could be used for genetic selection with disease-resistance varieties and upgradation of indigenous germplasm of domestic livestock.